1999 год. Осенняя сессия, 26 октября - 17 ноября - Теплова М. О. (2003)
Экземпляры: КХ (20060503) / Инвентарный номер: 1056455 / Цена: 20.00 / Сис.шифр: 67.400 / Авт.знак: Г 72 / ГРНТИ: 10 / ББК: 67.400.621